1999
DOI: 10.1093/fampra/16.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve cancer screening in general practice: are guidelines the answer?

Abstract: Young JM and Ward JE. Strategies to improve cancer screening in general practice: are guidelines the answer? Family Practice 1999; 16: 66-70. Background. GPs are ideally placed to recommend appropriate cancer screening for their patients. However, opportunities to discuss screening are often missed and screening procedures are not always recommended in accordance with national policy. The development of clinical practice guidelines represents one strategy for improving cancer screening in general practice.Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
(11 reference statements)
0
7
0
1
Order By: Relevance
“…In May 1999, 60 GPs who had participated in research about preventive care (Young 2000) completed a baseline self‐administered questionnaire about EBM. Questions adapted from existing quantitative instruments (McColl et al 1998; Young & Ward 1999a; Young & Ward 1999b) addressed views of EBM (using visual analogue scales), understanding of technical terms used in EBM, barriers to EBM in general practice, preferred strategies to support EBM, familiarity with the Cochrane Library and Internet and use of computers at work. Personal and professional details of participants also were ascertained.…”
Section: Methodsmentioning
confidence: 99%
“…In May 1999, 60 GPs who had participated in research about preventive care (Young 2000) completed a baseline self‐administered questionnaire about EBM. Questions adapted from existing quantitative instruments (McColl et al 1998; Young & Ward 1999a; Young & Ward 1999b) addressed views of EBM (using visual analogue scales), understanding of technical terms used in EBM, barriers to EBM in general practice, preferred strategies to support EBM, familiarity with the Cochrane Library and Internet and use of computers at work. Personal and professional details of participants also were ascertained.…”
Section: Methodsmentioning
confidence: 99%
“…Young et al showed that more than 40% of general practitioners reported that they were not aware of skin cancer screening guide-lines (40). Consequently, the establishment of national guide-lines might not be enough to improve cancer screening participation.…”
Section: Discussionmentioning
confidence: 99%
“…(19,20,34) Several studies have reported that clinical practice guidelines are difficult and inconvenient to use. (15,34,35) Thus, to promote an appropriate understanding of cancer screening guidelines, they should be presented in a format that is easy for health professionals to understand and use.…”
Section: Discussionmentioning
confidence: 99%
“…(7)(8)(9)(10) Several studies have reported that various health professionals have different levels of knowledge about cancer screening. (11)(12)(13)(14)(15)(16)(17) It is important that health professionals have the correct information to encourage individuals to participate in cancer screening programs.…”
mentioning
confidence: 99%